Ole Nørgaard and Lars Johannsen with Mette Skak and René Hauge Sørensen, The Baltic States After Independence, Cheltenham: Edward Elgar, 1999, 241 s., £ 55.00. - Jensen, Jens-Jørgen (Politica, 2000)
-